A Single-Dose Intramuscular Nanoparticle Vaccine With or Without Prior Intrauterine Priming Triggers Specific Uterine and Colostral Mucosal Antibodies and Systemic Immunity in Gilts but Not Passive Protection for Suckling Piglets - Choudhary, Pooja; Khajavinia, Amir; Mohammadi, Ramin; Ng, Siew Hon; Bérubé, Nathalie; Yalamati, Damayanthi; Haddadi, Azita; Wilson, Heather L. (Frontiers in Veterinary Science, 2022)
An effective single-dose vaccine that protects the dam and her suckling offspring against infectious disease would be widely beneficial to livestock animals. We assessed whether a single-dose intramuscular (i.m.) porcine epidemic diarrhea virus (PEDV) vaccine administered to the gilt 30 days post-breeding could generate mucosal and systemic immunity and sufficient colostral and mature milk antibodies to protect suckling piglets against infectious challenge. The vaccine was comprised of polymeric poly (lactide-co-glycolide) (PGLA)-nanoparticle (NP) encapsulating recombinant PEDV Spike protein 1 (PEDVS1) associated with ARC4 and ARC7 adjuvants, a muramyl dipeptide analogue and a monophosophoryl lipid A (MPLA) analogue, respectively (NP-PEDVS1). To establish whether prior mucosal exposure could augment the i.m. immune response and/or contribute to mucosal tolerance, gilts were immunized with the NP-PEDVS1 vaccine via the intrauterine route at breeding followed by the i.m. vaccine 30 days later. Archived colostrum from gilts that were challenged with low dose PEDV plus alum was used as positive reference samples for neutralizing antibodies and passive protection. At day 100 of gestation (70 days post i.m. immunization) both vaccinated groups showed significant PEDVS1 specific IgG and IgA in the serum, as well as in uterine tissue collected on the day of euthanasia. Anti-PEDVS1 colostral IgG antibody titres collected at farrowing were significantly higher relative to the negative control gilts indicating that the NP vaccine was effective in contributing the colostral antibodies. The PEDVS1-specific colostral IgA and anti-PEDVS1 IgG and IgA antibodies in the mature milk collected six days after farrowing were low for both vaccinated groups. No statistical differences between the vaccinated groups were observed suggesting that the i.u. priming vaccine did not induce mucosal tolerance. Piglets born to either group of vaccinated gilts did not receive sufficient neutralizing antibodies to protect them against infectious PEDV at 3 days of age. In summary, a single i.m. NP vaccine administered 30 days after breeding and a joint i.u./i.m. vaccine administered at breeding and 30 days post breeding induced significant anti-PEDVS1 immunity in systemic and mucosal sites but did not provide passive protection in suckling offspring.